Innovative Assessment Methods for the French Horn: Increasing the Effectiveness of Education - Zhou, Ning (Música Hodie, 2022)
The introduction of innovative assessment techniques for the French horn can improve the process of education. The objective is to examine the effectiveness of the proposed assessment methods for improving accuracy on the French horn. The research is based on the experimental design to evaluate the effectiveness of assessment methods using statistical data analysis and paired t-test. The research took place from January to June during the 2020-2021 academic year. The sample involved 183 students from three educational institutions in the People's Republic of China. A preliminary assessment found that the academic performance of students was low. Before the implementation of the proposed assessment methods, an average score was 20.63 points interpreted by the scholars as Do not Meet Academic Expectations. After the introduction of the assessment methods, the post-implementation scores of the academic performance increased by 41.3%. The findings were interpreted as a Satisfactory level of academic performance. The paired t-test revealed significant differences in student performance learning the French horn before and after the introduction of the new assessment methods. The average difference was 3.57 points. Thus, the proposed assessment methods for the French horn playing include (1) playing by ear, (2) Instrumental Scheme Processing, (3) a range practice, and (4) an introductory exam. The research demonstrates that the proposed assessment methods can be used as a part of the standard assessment developed for teachers that include different elements of effective teaching tools and methods.